Answer:
![\sf \left((f)/(g)\right)(x)=5-x](https://img.qammunity.org/2023/formulas/mathematics/high-school/7q7pg3e3p3wh7igpz637cjaczbddz3nnsq.png)
Explanation:
Given functions:
f(x) = 25 - x²
g(x) = x + 5
Difference of Perfect Squares rule: a² - b² = (a + b)×(a - b)
1. Rewrite function f(x) using the rule:
5 × 5 = 25 ⇒ 5²
x × x = x²
f(x) = 5² - x² ⇒ f(x) = (5 + x)×(5 - x)
2. Divide and simplify:
![\sf\left((f)/(g)\right)(x) =(f(x))/(g(x))\\\\\left((f)/(g)\right)(x)=((5 + x)(5 - x))/(x+5)\\\\\left((f)/(g)\right)(x)=5-x](https://img.qammunity.org/2023/formulas/mathematics/high-school/rz9wd7hgcclfh114ye2lst9mhea26stdfr.png)